Determinant Factors of Intention to Pay Zakat, Infaq and Shadaqah in Dompet Peduli Umat Daarut Tauhid - Sawqi Saad El Hasan; Muhammad Salman Al Farisi (Sharia Business Management Department of STEBIS Bina Mandiri, 2022)
Zakat, infaq and shadaqoh are economic instruments that will be more useful if channeled through amil zakat institutions. With the programs offered, DPU-DT distributes ZIS funds in the form of empowerment which includes a productive economy, educational scholarships, and free health which are managed systematically, intensively, and continuously. The large number of existing LAZs requires zakat amil to be able to formulate strategies to attract muzakki to channel ZIS funds to them. This study aims to determine what factors influence muzakki's interest in distributing Zakat, infaq and shodaqoh of DPU-DT. The research method used is descriptive quantitative analysis with factor analysis tools. Based on the seven variables, namely: trust, service, program, transparency of funds, office location, network, and professionalism of the institution, then developed into 20 questions that have conformity with the seven variables. Factor analysis was used to test 20 variables based on the similarity of the analyzed variables. The test results of 20 variables that pass and are eligible to be processed to the next stage are that only 13 variables met the criteria to be processed and resulted in 4 dominant factors influencing the interest of muzakki in distributing ZIS to DPU-DT